Constitutionalism and the new Zimbabwean Constitution - Madebwe, Tinashe (Midlands State University, 2016)
Codified constitutions are arguably the most celebrated type of Constitution in the world.1 This is probably because codified Constitutions are contained in one document called 'The Constitution.'2 As such, they offer a primary and singular source from which 'constitutional' provisions can be gleamed, making such Constitutions accessible and clear to citizens and to the world at large.3 Beyond this however, codified Constitutions are also celebrated because of their symbolic value.4 Here, it is worthwhile to consider that codified Constitutions typically emerge, and succeed, following an upheaval, the classical example of which is a revolution.5 As such, codified Constitutions are celebrated partly because they represent the turn to new constitutional dispensations in which things will be 'different' from the way they were previously. This symbolism is not to be discounted. Various states, most recently South Africa and Iraq, have relied on the symbolic value that codified Constitutions hold as the backbone for the transition to constitutional democracies which have united peoples across the nation and been regarded as a beacon of hope and change